PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP ORGANIZATIONAL PERFORMANCE MELALUI ORGANIZATIONAL CULTURE DAN ENTREPRENEURIAL INTENSITY SEBAGAI INTERVENING VARIABLE PADA PERUSAHAAN PUBLIK DI SURABAYA - Jessica, Helena (Business Accounting Review, 2015)
The aimed of this study was to examine the relationship of transformational leadership to the firm performance. This research was conducted in order to find the affect of transformational leadership through organizational culture and entrepreneurial intensity as the intervening variables. This study used primary data obtained from questionnaires distributed to go-public companiesâ employees in Surabaya. The samples were companies that used transformational leadership. Based on the multiplication of the question of the variable items obeserved 4 or 5 times a sample of 147 employees was set of in 30 companies that use transformational leadership. The test results showed that the application of transformational leadership gave a positive and significant influence on the firm performance. But, Entrepreneurial intensity didnât provide a positive impact on the firm performance and there was no significant influence of organizational culture on firm performance. Therefore transformational leadership provided a significant influence on firm performance through entrepreneurial intensity.